Effect Of Chitosan On Biochemical And Microbial Quality Of Minimally Processed Mango (Mangifera Indica L.) Cubes During Storage (Applied Biological Research, 2018)
Fresh-cut mango cubes of cultivar “Mallika” coated with acidified chitosan  solutions at three concentrations (1, 2 and 3%) along with untreated cubes as  ontrol were placed into plastic trays, over-wrapped with cling film (10 µ thickness) were stored in refrigerator at 8±2oC for 8 days and analyzed for  quality parameters after 2, 4, 6 and 8 days. Chitosan coatings, especially 2 and 3%, were effective in inhibiting weight loss, total carotenoids and total  phenols contents. Chitosan 3% coating was highly effective in inhibiting the growth of bacteria and yeast/mould on cubes. At the end of storage period,  the minimum weight loss (2.46%) was observed in 3% chitosan-treated cubes  and maximum (4.51%) in control. High total phenol content (41.79 mg TAE  100 g-1) was observed in 2% chitosan-treated samples. Maximum total  carotenoids content (5.35 mg 100 g-1) was observed in 3% chitosan treatment.  Higher total soluble solid (25.6° Brix) was found in control. Minimum  bacterial load (2.04 log cfu g-1) and yeast/mould load (1.78 log cfu g-1) was  observed in 3% chitosan-treatment while bacterial load (log CFU g-1) and  yeast/mould count was high in (3.02 and 3.92 log CFU g-1, respectively, was in  control. The results suggest that 3% chitosan coating on mango cubes  effectively minimized weight loss, biochemical changes and microbial growth.
Keywords: Biochemical changes; edible coatings; mango cubes; microbial quality